1981
DOI: 10.1029/gl008i009p00987
|View full text |Cite
|
Sign up to set email alerts
|

Ion jetting at the plasma sheet boundary: Simultaneous observations of incident and reflected particles

Abstract: Data which show energetic ions jetting towards the earth at the plasma sheet boundary are presented. The ions are spatially dispersed such that the most energetic particles lie furthest from the neutral sheet. Simultaneously, non‐thermal ion spectra were seen in the small particle fluxes moving from the earth. These particles are believed to be the earthward jetting ions after their reflection near the earth. We argue that these dispersion effects result from a combination of a tailward moving source and a cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 7 publications
3
21
0
Order By: Relevance
“…[1979] demonstrated that the vertical motion of the plasma sheet has velocities ranging from 10 to 60 kmls. This was later confirmed by Andrews et al [1981], Forbes et al [1981a, b], and Eastman et at. [1985].…”
Section: -0227195195ja-00902$0500supporting
confidence: 74%
See 1 more Smart Citation
“…[1979] demonstrated that the vertical motion of the plasma sheet has velocities ranging from 10 to 60 kmls. This was later confirmed by Andrews et al [1981], Forbes et al [1981a, b], and Eastman et at. [1985].…”
Section: -0227195195ja-00902$0500supporting
confidence: 74%
“…A number of studies [Mobius. et al, 1980;Andrews et al, 1981;Williams, 1981;Eastman et at., 1984Eastman et at., , 1985Takahashi and Hones, 1988] have established that the PSBL is nearly always present, and velocities as high as 1000 kmls are detected even during quiet times [Takahashi and Hones, 1988]. Takahashi and Hones [1988] estimated that the outermost 19,192 ASHOUR-ABDALLA ET AL.…”
Section: -0227195195ja-00902$0500mentioning
confidence: 99%
“…Sauvaud et al 1999;Sergeev et al 2000b). Ion energy dispersion in such structures is basically formed as a result of three main effects: (1) the pure time-of-flight (TOF) effect, which spreads ions of different energies along the magnetic field line; (2) the VF effect due to magnetotail E × B convection, which produces an equatorward drift of accelerated ions while they propagate from their source to the Earth (Andrews et al 1981;Williams 1981); and (3) the "place of birth" (PB) effect related to the ion acceleration mechanism whose efficiency might depend on the local conditions in the CS, such that the energy gained by the ions during their interaction with the CS may vary with location (Ashour-Abdalla et al 1993). The VF effect produces a spatial structuring (layering) of ions according to their energy value, with the highest-energy ions appearing closest to the lobeward edge of PSBL and lower energy ions showing deeper in the PSBL (e.g.…”
Section: Possible Auroral Manifestations Of Psbl Ion Beamsmentioning
confidence: 99%
“…From the detailed observation, of a multiple encounter with this layer of flowing plasma they infer either a multiple a tructure or a wave-like modulation of the plasma sheet boundary surface. Andrews et al (1981) have observed, on ISEE-2 at ti15 RE , a structured layer of ions between 25 keV and 2.5 MeV jetting towards the Earth at the plasma sheet boundary, together with the tailward return flow of mirroring ions. The energy dispersion characteristics of these ions are explained as the effects of their flow in the magnetotail E field and of the motion of their source.…”
Section: Introductionmentioning
confidence: 99%